2017
DOI: 10.1111/nmo.13191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remifentanil on esophageal and esophagogastric junction (EGJ) bolus transit in healthy volunteers using novel pressure‐flow analysis

Abstract: Remifentanil-induced effects were different for proximal and distal esophagus, with a reduced time for trans-sphincteric bolus flow at the EGJ, suggestive of central and peripheral μ-opioid agonism. There were no functional consequences in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Previous research observed that chronic opioid use also affected esophageal function, causing symptoms of dysphagia and a manometric pattern of functional esophagogastric junction-outflow obstruction (EGJ-OO) and achalasia assessed by high-resolution manometry (HRM). [6][7][8] More recently, Ortiz et al postulated a new entity known as opioid-induced esophageal dysfunction (OIED) referring to esophageal motility disorders caused by chronic use of opioids. 9 It was also observed that the prevalence of OIED is higher in patients taking higher doses of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research observed that chronic opioid use also affected esophageal function, causing symptoms of dysphagia and a manometric pattern of functional esophagogastric junction-outflow obstruction (EGJ-OO) and achalasia assessed by high-resolution manometry (HRM). [6][7][8] More recently, Ortiz et al postulated a new entity known as opioid-induced esophageal dysfunction (OIED) referring to esophageal motility disorders caused by chronic use of opioids. 9 It was also observed that the prevalence of OIED is higher in patients taking higher doses of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Intravenous remifentanil was reported to increase LES relaxation pressures (IRP) and reduce distal latencies in healthy volunteers in 1 study, 19 while another study reported no associated change in IRP, but a reduction in distal latency measures. 20 This latter study also demonstrated a reduction in trans-EGJ bolus flow utilizing the BFT after remifentanil. 20 Studies assessing the effect of intravenous midazolam on esophageal motility have yielded inconsistent results: one demonstrated increased basal EGJ pressure and increased LES relaxation pressures among healthy asymptomatic adults, 9 while another demonstrated no changes in LES pressures among pediatric patients.…”
Section: Discussionmentioning
confidence: 68%
“…20 This latter study also demonstrated a reduction in trans-EGJ bolus flow utilizing the BFT after remifentanil. 20 Studies assessing the effect of intravenous midazolam on esophageal motility have yielded inconsistent results: one demonstrated increased basal EGJ pressure and increased LES relaxation pressures among healthy asymptomatic adults, 9 while another demonstrated no changes in LES pressures among pediatric patients. 10 Overall, while previous studies reported changes in esophageal motility parameters with administration of intravenous opioids or benzodiazepine generally among healthy volunteers, there were some inconsistencies in findings between studies and all of the studies were reported using experimental conditions.…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies utilizing HRM have shown that opioids use increased LES pressure and is associated with hypercontractility. 15,23,[26][27][28] A large sample size series conducted by Ratuapli et al 15 further demonstrated an association between chronic opioid use and esophageal motor dysfunction. They found that the main opioid-related esophageal disorders are EGJOO and type III achalasia, and the other dysmotility described are distal esophageal spasm (DES) and hypercontractile esophagus, a clinical entity which has been termed opioid-induced esophageal dysfunction (OIED).…”
Section: Discussionmentioning
confidence: 98%